2010
DOI: 10.3233/jae-2010-1195
|View full text |Cite
|
Sign up to set email alerts
|

A study of magnetic fluid seals for underwater robotic vehicles

Abstract: Underwater robotic vehicles (URVs) normally use mechanical seals with o-rings, rubber boots, PTFE or Grafoil wedges, or V-rings. Because mechanical seals can cause an unexpected malfunction, we try to adapt magnetic fluid seal (MFS) for underwater robotic vehicles. For reliable design of the MFS, we use numerical simulation of the flow in the MFS using finite element method. The results obtained from experimental investigations of the operation of the MFS contacting with pressurized water will be compared to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…At present, lots of research studies focus on OMS with less than 0.4 mm small clearance. Urreta and Mkubik et al analyzed the sealing effect of two kinds of magnetofluid with different particle sizes to improve the pressure ability and to reduce friction torque and apply them to the spindle of high-precision machine tool [6,7]. Zhang et al studied and analyzed the influence of volume fraction of magnetofluid, magnetic field parameters, geometrical parameters, and different ester magnetofluids on the sealing ability of OMS [8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, lots of research studies focus on OMS with less than 0.4 mm small clearance. Urreta and Mkubik et al analyzed the sealing effect of two kinds of magnetofluid with different particle sizes to improve the pressure ability and to reduce friction torque and apply them to the spindle of high-precision machine tool [6,7]. Zhang et al studied and analyzed the influence of volume fraction of magnetofluid, magnetic field parameters, geometrical parameters, and different ester magnetofluids on the sealing ability of OMS [8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al (2016) experimentally studied the lubrication characteristics of the ferrofluid film in a spiral groove mechanical sea, and revealed that the hydrodynamic pressure increases with the increasing magnetic field intensity. The viscosity of lubricant film has a very important influence on the performance and leakage rate in a non-contacting mechanical seal (Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This combination of fluidic and magnetic properties of the ferrofluid is exploited in many innovative engineering devices. Examples of ferrofluid-based devices are seals for underwater robotic vehicles [1] and rotary blood pumps [2], also sensors for acceleration [3,4], pressure [5] and fluid flow [6].…”
Section: Introductionmentioning
confidence: 99%